2007
DOI: 10.1002/cbdv.200790041
|View full text |Cite
|
Sign up to set email alerts
|

2,2′,4‐Trihydroxybenzophenone: Crystal Structure, and Anti‐Inflammatory and Antioxidant Activities

Abstract: The crystal structure of '2,2',4-trihydroxybenzophenone' (=(2,4-dihydroxyphenyl)(2-hydroxyphenyl)methanone; 1) was determined, and its molecular structure, along with intra- and intermolecular H-bonds, was analyzed. The anti-inflammatory potential of 1, evaluated by means of the rat-paw-edema assay, with carrageenan as inflammation stimulus, was found to be similar high as that of indomethacin. In contrast, benzophenone proper (2) was hardly active in this assay. Our results indicate that these anti-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 23 publications
4
23
0
Order By: Relevance
“…The shortening of certain aromatic C-C distances is reported in a series of related benzophenones. 30,31 Nevertheless, the aromatic distances found in (a) are in agreement with the range required for aromatic bonds, just as all aromatical C-C-C angles (mean of 120(4)°) coincided with the reference corners for the aromatic ring. In the same way, the C-C single and double bonds at the prenyl fragments present concordant distances in relation to similar prenylated compounds (mean distances of 1.311(4) Å for C=C, 1.500(4) Å for C sp 3 -C sp 2 and 1.549(5) Å for C sp 3 -C sp 3 ).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The shortening of certain aromatic C-C distances is reported in a series of related benzophenones. 30,31 Nevertheless, the aromatic distances found in (a) are in agreement with the range required for aromatic bonds, just as all aromatical C-C-C angles (mean of 120(4)°) coincided with the reference corners for the aromatic ring. In the same way, the C-C single and double bonds at the prenyl fragments present concordant distances in relation to similar prenylated compounds (mean distances of 1.311(4) Å for C=C, 1.500(4) Å for C sp 3 -C sp 2 and 1.549(5) Å for C sp 3 -C sp 3 ).…”
Section: Resultssupporting
confidence: 66%
“…These features are consequence of entire electronic delocalization through the atoms O2-C10-C3-C4-O1 that in solution lead to distinct tautomeric forms. 1,2,30 However, in the (a) crystal structure the model considering the C10-OH2 tautomer gives the best fitted final refinement indexes. In this way, from a statistical point of view revelled by XRD analysis, this model must be taken in account in the moment of structural assignments by NMR spectroscopic techniques performed in solution.…”
Section: Resultsmentioning
confidence: 99%
“…The 2,2',4-trihydroxybenzophenone was capable of inhibiting the inflammatory process, reducing the diameter of the edema by 47.0 ± 10% after 2 h, and 34.0 ± 6% after 3 h. The 2,2',4-trihydroxybenzophenone showed similar efficacy for inhibition of rat-paw-edema than indomethacin, which inhibited the edematogenic process by 43.0 ± 4%, 51.0 ± 7%, and 52.0 ± 5% after 2, 3 and 4 h, respectively. 36 As stated above, serine-proteases, such as elastase, play an important role in inflammatory processes. Thus, these enzymes are targeted to explore in the direction of research and development of more effective anti-inflammatory compounds that can be employed in the therapeutic.…”
Section: Introductionmentioning
confidence: 98%
“…28,29 Several studies have shown the efficacy of triazole as potent elastase inhibitors. 30 Our research group has been involved in investigating several synthetic [33][34][35][36][37] and natural 38 benzophenones. For instance, the anti-inflammatory potential of 2,2',4-trihydroxybenzophenone was assessed by means of the rat-paw-edema induced by carrageenan application assay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation